THE CAUSAL FACTORS OF BUGIS-BONE ACCENT INTERFERENCE ON THE PRONUNCIATION IN ENGLISH CONVERSATION - Nur Fadhillah; Hamdan Juhannis; Sitti Nurpahmi (Universitas Islam Negeri Alauddin Makassar, 2018)
The research was purposed to identify the causal factors of the English Students’ Accent interference on the pronunciation in English conversation. To meet the objective, the researcher adopted case study design by Cresswell. The data were gathered through qualitative method based on Miles and Huberman’s technique of data analysis. The research was undertaken in STAIN Watampone, Kabupaten Bone, from March 2017 to May 2017. The finding of the research showed that the the different phoneme areas of Bugis-Speaker with English Speakers and Bugis-Bone is strong/heavy accent are the causal factors that become the interference when the students speak English in English conversation. Referring on the description above, it informed that the students must be aware of their first language interference to their English pronunciation in English conversation.